Physical Learning Environment, Learning Motivation, and Technical Competence among Heavy Equipment Vocational Students: A Mediation Analysis - I Putu Redy Irawan; Iswahyudi Indra Putra (Fakultas Teknik, Universitas Negeri Makassar, 2026)
Purpose – A supportive physical learning environment is an important component of vocational education because it enhances practical learning experiences and facilitates the development of industry-relevant competencies. This study examines how the physical learning environment contributes to students’ technical competence through the role of learning motivation. Methods – An explanatory quantitative design was employed involving 120 Heavy Equipment Engineering vocational students selected through purposive sampling. Data were collected using a structured questionnaire and analyzed using SPSS Statistics with Hayes’ PROCESS Macro Model 4. Findings – The results indicate that the physical learning environment positively influences both learning motivation and technical competence. Learning motivation was also found to function as an explanatory mechanism linking the physical learning environment to technical competence. The proposed model yielded an R² value of 0.9062, suggesting substantial explanatory power within the present sample. However, this finding should be interpreted cautiously because the analysis relied on self-reported data and did not include other contextual or individual factors that may also affect competency development. Overall, the findings highlight the importance of supportive learning conditions and student motivation in enhancing technical competence in vocational education. Research implications – Although the study was limited to Heavy Equipment Engineering students in Sorong and relied on perception-based data, the findings suggest that improving learning facilities and strengthening student motivation should be prioritized in practice-based vocational education. Originality – This study contributes to the vocational education literature by identifying learning motivation as a mechanism through which the physical learning environment influences technical competence, providing evidence from a vocational context that has received limited empirical attention.